TRIBOLOGICAL PROPERTIES OF COCRFEW ALLOY UNDER SEAWATER CONDITION (MT) - WANG XiaoBo; CUI GongJun; LI FangZhou; CHENG ShuShuai (Jixie qiangdu)
In this study, CoCrFe-based alloys reinforced by W（0 wt%, 4 wt%, 8 wt% and 12 wt%） were prepared by powder metallurgy, and the tribological properties of the alloys under seawater environment were systematically studied. The friction and wear behavior of the alloy under different loads and sliding speeds in seawater was studied using a reciprocating ball-on-disk friction and wear tester sliding against with GCr15 steel ball; X-ray diffractometer, scanning electron microscope and energy dispersive x-ray analyzer were used to analyze the phase composition and wear mechanisms of the alloys. The results show that the CoCrFeW alloy is composed of ε（hcp）, γ（fcc）, Fe-Cr and Cr2O3 phases. The alloy structure was compact, and the hardness and density increased with the increase of W content. Generally speaking, the friction coefficients of the alloy showed a decreasing trend with the increase of sliding speed and load, and increased first and then decreased with the increase of W content under high-speed conditions. Under high load conditions, the friction coefficients of W-added specimens first decreased and then increased with the increase of W content. The wear rates decreased with the increase of sliding speed, load and W content. Seawater component reaction products and alloy corrosion products had friction-reducing and antiwear action. W significantly improved the wear resistance of the alloy in seawater environment, and the specimen CW8 with 8 wt%W added showed the best tribological performance. As the W content increased, the alloy wear mechanisms changed from plastic deformation and fatigue wear to abrasive wear.